Enhanced phosphorylation of sphingosine and ceramide sustains the exuberant proliferation of endothelial progenitors in Kaposi sarcoma. Issue 3 (15th December 2017) - Abdel Hadi, Loubna; Calcaterra, Francesca; Brambilla, Lucia; Carenza, Claudia; Marfia, Giovanni; Della Bella, Silvia; Riboni, Laura
Abstract: Endothelial colony‐forming cells (ECFCs), a unique endothelial stem cell population, are highly increased in the blood of Kaposi sarcoma (KS) patients. KS‐derived ECFCs (KS‐ECFCs) are also endowed with increased proliferative and vasculogenic potential, thus suggesting that they may be precursors of KS spindle cells. However, the mechanisms underlying the increased proliferative activity of KS‐ECFCs remain poorly understood. Sphingosine‐1‐phosphate (S1P) and ceramide‐1‐phosphate (C1P) are metabolically interconnected sphingoid mediators crucial to cell proliferation. Here, we investigated the metabolism, release, and proliferative effects of S1P and C1P in KS‐ECFCs compared with control ECFCs (Ct‐ECFCs). Metabolic studies by cell labeling, chromatographic analyses, and digital autoradiography revealed that S1P and C1P biosynthesis and S1P secretion are all efficient processes in KS‐ECFCs, more efficient in KS‐ECFCs than Ct‐ECFCs. Quantitative PCR analyses demonstrated a significantly higher ceramide kinase and sphingosine kinase‐2 expression in KS‐ECFCs. Notably, also the expression of S1P1 and S1P3 receptors was augmented in KS‐ECFCs. Accordingly, treatment with exogenous C1P or S1P induced a significant, concentration‐dependent stimulation of KS‐ECFC proliferation, but was almost completely ineffective in Ct‐ECFCs. Hence, we identified C1P and S1P as autocrine/paracrine proliferative signals in KS‐ECFCs. A better understanding of the mechanisms that enhance S1P/C1P formation in KS‐ECFCs may yield effective therapeutic modalities.